Analisis Literatur Tentang Gelombang Elektromagnetik Dan Pengaruhnya Pada Teknologi Komunikasi - Ziliwu, Hadirat Syukur; Gulo , Frans Alpinter; Waruwu, Fatman Juang Putra (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
In this aspect, electromagnetic waves are physical phenomena that play an important role in the progress of the present communication system. This paper reviews the literature on the characteristics of electromagnetic waves, how the waves affect data networks, wireless systems, and telecommunications between other fields of communication technology. Research shows that electromagnetic waves allow shipping information efficiently through cables, air, and other media. Wave frequency transition from radio to millimeter waves has opened a new path for network speed and capacity. However, a number of interference, safety, and health effects began to emerge. The findings above there is no doubt highlighting the fact that a deep understanding of electromagnetic waves forms the basis of innovation and the development of communication technology on a sustainable manner. Electromagnetic Physical phenomena that carry out the progress of this make review through cables, and other media. Wave frequency transition from radio to millimeter waves has opened the barudan capacity path. However, a number of problems of disruption, safety, and health impact arise. The above findings are undoubtedly highlighting the fact that a deep understanding of electromagnetic waves forms the basis of innovation and building communication technology on a sustainable manner.